In vitro and in situ activity of carboxymethyl cellulase and glutamate dehydrogenase according to supplementation with different nitrogenous compounds - Carvalho, Isabela Pena Carvalho de [UNESP]; Detmann, Edenio; Paulino, Mário Fonseca; Mantovani, Hilário Cuquetto; Valadares Filho, Sebastião de Campos; Gomes, Daiany Iris; Costa, Viviane Aparecida Carli (Sociedade Brasileira de Zootecnia, 2012)
Two experiments were carried out to evaluate the effect of supplementation with different nitrogenous compounds on the activities of carboxymethil cellulase (CMCase) and glutamate dehydrogenase (GDH). In the first experiment, four treatments were evaluated in vitro: cellulose, cellulose with casein, cellulose with urea, and cellulose with casamino acids. After 6, 12 and 24 hours of incubation, CMCase and GDH activity, pH, and concentrations of ammonia nitrogen (AN) and microbial protein were measured. In the three incubation periods, the concentration of AN was higher when urea was used as a supplemental source of nitrogen. The activity of CMCase was higher with the addition of urea and casamino acids when compared with the control and the casein treatment. Supplementation with casamino acids provided higher GDH activity when compared with the control at 6 hours of incubation. At 12 hours of incubation, the GHD activity was also stimulated by casein. At 24 hours, there was no difference in GHD activity among treatments. In the second experiment, three rumen-fistulated bulls were used for in situ evaluation. Animals were fed Tifton hay (Cynodon sp.) ad libitum. The treatments consisted of control (no supplementation), supplementation with non-protein nitrogenous compounds (urea and ammonium sulphate, 9:1) and supplementation with protein (albumin). In treatments with nitrogenous compound supplementation, 1 g of crude protein/kg of body weight was supplied. The experiment was conducted in a 3 × 3 Latin square design. The measurements were performed at 6, 12 and 24 hours after supplementation. No difference in GDH activity was observed among treatments. The control treatment showed higher CMCase activity when compared with the treatments containing supplemental sources of nitrogen. However, urea supplementation provided higher CMCase activity compared to albumin.
Keywords: fibrolytic enzymes; nitrogen assimilation; protein effect; rumen microbiology